Social work in Ukraine: development trends and problems before and during the war with Russia - Yevdokymova, Iryna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
The article is devoted to the analysis of development trends and problems of social work in Ukraine before and during the war with Russia. Using the method of historical analogy, the author examines the main trends and problems of the development of social work in Ukraine. Poland was chosen as a country that is culturally, historically, politically, economically and socially close to Ukraine. The article notes that there is a certain lag between the passage of the main stages in the development of social work in Ukraine and Poland. As the main trends in the development of social work in Ukraine before the start of military aggression by Russia, the article highlights the development of integrated social services and social work in communities, the establishment of effective professional training of social workers for work in local social services, etc. The main problems of pre-war social work include the lack of personnel for social agencies, the low level of prestige and wages of social workers compared to representatives of other professions, the lagging of formal education systems from the needs of professional activity, etc.Russia's military aggression made certain adjustments to social work in Ukraine and Poland. According to the results of the interview of managers and leading specialists of social agencies of the city of Kharkiv, as well as Sumy, Poltava and Dnipropetrovsk regions, which was conducted by the Department of Sociology of Management and Social Work of the School of Sociology of V. N. Karazin Kharkiv National University in November 2022, the main problems of activities of social workers in Ukraine are the absence of generally safe working conditions, as well as the absence of conditions for the performance of their official duties, insufficient personnel and/or their overload. In Poland, however, there were problems with establishing communication with forcibly displaced persons, it was also actualized the practices of providing psychological assistance to war victims, the workload of the personnel of social agencies increased significantly and others. The article concludes that the war with Russia and the problems in the activities of social agencies in Ukraine, to which it led, became a significant challenge for social work, capable to change the trends of its development